Distance course "Information systems and technology" for speciality "Tourism" - E. A. Kosova (Academy of Cognitive and Natural Sciences, 2014)
Research goals: to consider an alternative methodical approach for the development of remote practical course on the subject "Information systems and technologies" for students of 'Tourism' speciality. Research objectives: to study methodical literature and content of on-topic remote educational courses; to develop a guidelines for practical courses; to verify a technique of remote practical courses in experiment; and to incorporate new recommendations into educational process. Object of research: the educational process for future specialists in 'Tourism' in the direction of the conscious use of information systems and technologies. Subject of research: development of information and communication competencies of first year students of 'Tourism' speciality. Research methods used: theoretical - analysis of scientific and methodical literature, operational and educational programs in informatics, curricula and standards; empirical - training, supervision on the educational process, testing of student's competence level. Results of the research: the guidelines for practical courses on the subject "Information systems and technologies" for the students of 'tourism' speciality were developed, tested and implemented; respective remote course was developed on the basis of the Moodle virtual training system. The practical courses are interdisciplinary, oriented to the didactic principles of activity, consciousness and self-consistency, and independent of specific software. The main conclusions and recommendations. The testing of the study results has confirmed the success of the developed course. It is planned to continue the work towards development of theremote course "Hypertext markup language. Design of web pages for tourist organizations".